Building Expectations and Keeping Customers Happy: How Charter School Leaders Recruit and Retain Families. Issue 2 (3rd April 2022) - Riel, Virginia
ABSTRACT: Using qualitative data collected in three charter schools over the course of 14 months, this article analyzes how involvement expectations played a role in charter school recruitment practices and shaped personnel-parent relations. Through various recruitment strategies, personnel built involvement expectations among prospective parents, treating them as valued customers whose happiness carried consequences for funding. Personnel drew on parents' financial networks, neighborhood connections, and social media contacts to recruit families, as for-profit charter school budgets rely on the recruitment and retention of parents who can volunteer, serve on committees, provide transportation, court donors, and recruit similar families.